Detection of Cryptosporidium‎‎ spp in Bobwhite Quails (Coturnix coturnix) by ‎Traditional Methods in Baghdad City, Iraq - yahya, khitam jasim; Al-Zubaidi, Mohammed Thabit Salih (The Iraqi Journal of Veterinary Medicine, 2023)
Cryptosporidiosis is one of the most important zoonosis diseases distributed ‎worldwide causes severe diarrhea in animals and is lethal in quails. This study detected ‎Cryptosporidium‎‎ spp. in quails in Baghdad province Iraq by flotation and staining methods ‎and compared these results with PCR results from the previous study. This research was ‎carried out from January 2022 to September 2022. Out of 180 quails (Coturnix coturnix) in ‎total were investigated. The overall infection rate of Cryptosporidium‎‎ spp. in quails was ‎‎23.9% (43/180). Young quail had a greater infection rate of 44.2% (19/43) while adult ‎quails had a lower infection rate of 17.2% (24/137). Finding from the research revealed that there were ‎no significant differences between males and females and highly significant differences ‎among the months of study with the highest infection rate being 45% (9/20) in April, and ‎the lowest infection rate being 10% in June and July. This disease was presented in birds ‎and birds act as a mechanical carrier of Cryptosporidium‎‎ spp. between a conventional acid-‎fast staining procedure and PCR test, PCR can not only detect Cryptosporidium‎‎ but is also ‎able to differentiate between what appear to be host-adapted genotypes of the parasite with ‎high sensitivity and specificity‎‎‎.